PENERAPAN MODEL PEMBELAJARAN STRUCTURED NUMBERED HEADS (KEPALA BERNOMOR TERSTRUKTUR) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X MIA SMAN 5 PEKANBARU - Putra, Mardiansyah; ', Rini; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the application of the Structured Numbered Heads learning model was done to improve students learning achievement in the topics of the atomic structure and the periodic system of elements in class X MIA SMAN 5 Pekanbaru. This research was experiment based on pretest-posttest design. The sample consisted of two classes, which are X MIA 4 as experiment class and X MIA 3 as control clas that randomly selected after testing normality and homogeneity. Experiment class was a class treated by applying the Structured Numbered Heads learning model. Analyzed of data used t-test. Results of the analysis it was found that tscore>ttable (3,58>1,67), it means the Structured Numbered Heads learning model can improve students learning achievement on the structure of atoms and the periodic system of elements in class X MIA SMAN 5 Pekanbaru with an increase of 14,14%.Key Words: Research on the application of the Structured Numbered Heads learning model,Learning achievement